Voice Behavior as a Key Driven Organizational Commitment and Employee Involvement Toward Organizational Change - Iskandar, Andri; Daryono, ‎; Zacharias, Tehubijuluw; Wulandari, Florentina Ratih (KnE Social Sciences, 2025)
This study aims to determine and analyze (1) the effect of organizational commitment on organizational change through employee voice behavior and (2) the effect of employee involvement on organizational change through employee voice behavior of the Regional Revenue Agency of the Aru Islands Regency. This study uses a descriptive-quantitative approach with a causal correlation type conducted at the Regional Revenue Agency of the Aru Islands Regency for 2 months, namely April and May 2024. The population used in this study were employees of the Regional Revenue Agency of the Aru Islands Regency, totaling 35 people. The sample is part of the number and characteristics possessed by the population. The sampling method is full sampling. Data were analyzed using path analysis. The results of the study concluded that organizational commitment and employee involvement have a positive and significant effect on voice behavior, which plays an important role in driving organizational change. However, organizational change is not directly influenced by employee commitment and involvement, but rather by the extent to which they dare to voice ideas and opinions. Therefore, organizations need to strengthen voice behavior by creating an environment that supports active participation and innovation so that change can run more effectively.